2012
DOI: 10.1590/s1415-43662012000700011
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de óleo no controle de Zabrotes subfasciatus e na germinação de Phaseolus vulgaris

Abstract: R ESU M OPropôs-se, com este trabalho, estudar a qualidade de sementes de feijão carioca (Phaseolus vulgaris L.) tratadas com óleos vegetais de mamona, soja e oiticica, durante cinco meses de armazenamento. Mediante os resultados obtidos concluiu-se que os óleos vegetais utilizados no tratamento das sementes de feijão Phaseolus foram eficientes na manutenção da viabilidade e no controle da infestação pelo inseto-praga de armazenamento Zabrotes subfasciatus, nos cinco meses de armazenamento, sendo o óleo de oit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…This outcome is very relevant, once it evidenced that the alternative treatments tested in this study had almost no detrimental effects on the physiologic quality of bean seeds. Many authors have reported the use of powders, extracts, and oils from plants with insecticide properties for controlling weevils, once they inhibit the action of bruchids without damaging the seeds (Mateus et al, 2017;Girão Filho et al, 2014;Borsonaro et al, 2013;Silva et al, 2013a;Silva et al, 2013b;Queiroga et al, 2012;Garcia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome is very relevant, once it evidenced that the alternative treatments tested in this study had almost no detrimental effects on the physiologic quality of bean seeds. Many authors have reported the use of powders, extracts, and oils from plants with insecticide properties for controlling weevils, once they inhibit the action of bruchids without damaging the seeds (Mateus et al, 2017;Girão Filho et al, 2014;Borsonaro et al, 2013;Silva et al, 2013a;Silva et al, 2013b;Queiroga et al, 2012;Garcia et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Due to health and environmental problems associated to synthetic chemical compounds used to control weevil in stored seeds and grains, researches have recently focused their efforts on finding alternative substances that have less impact on non-target organisms (Lima-Mendonça et al, 2013;Ootani et al, 2013). Among the studied possibilities, animal and vegetable oils (Mateus et al, 2017;Campos et al, 2014), diatomaceous earth (Lima et al, 2014;Silva et al, 2012), and dry powdered plant products (Melo et al, 2014) have stood out, owing to their potential of use.…”
Section: Introductionmentioning
confidence: 99%
“…The clove plant, known by its distinctive aroma, has in its compound eugenol, commonly used as an antimicrobial and antifungal. Aromatic plants may have repellent effect on insects that had been already proven in form of essential oils (Maia & Parente Júnior, 2008;Guerra et al ;Migliorini et al, 2010;Fazolin et al, 2010;Pinto Júnior et al, 2010;Coitinho et al, 2011;Queiroga et al, 2012;Ootani et al, 2013), and also on insects of stored seeds and grains.…”
Section: Introductionmentioning
confidence: 98%
“…Plantas de diversas famílias têm se mostrado promissoras para o controle de insetos-praga de grãos armazenados como: Anacardeaceae e Euphorbiaceae com espécies de importância econômica encontradas na região da Caatinga ainda pouco estudadas e a Lamiaceae muito utilizada e que já possui diversas substâncias conhecidas e estudadas como fungicida e inseticida (Souza et al, 2010;Coitinho et al, 2011;Ootani et al, 2011;Hameed et al, 2012;Queiroga et al, 2012). Objetivou-se, portanto, com este trabalho, avaliar o efeito tóxico e repelente dos óleos essenciais de Croton heliotropiifolius Kunth, Croton pulegiodorus Baill, Myracrodruon urundeuva Allemão e Ocimum basilicum L. sobre Zabrotes subfasciatus praga do feijão-comum (Phaseolus vulgaris) armazenado.…”
Section: Introductionunclassified